INOVASI PELAYANAN ADMINDUK SECARA ONLINE DENGAN APLIKASI “BAKSO” DI DISDUKCAPIL LOMBOK TIMUR - Masbullah (KOLONI, 2022)
This online service innovation research with the "BAKSO" application at the Disdukcapil East Lombok aims to find out the problems behind the creation of an online population administration system at the Disdukcapil East Lombok. In addition, this study aims to determine the application of an online application system in population administration registration services in East Lombok Regency. This study uses the theory of public service and service innovation. The method used in this study is a qualitative descriptive method with data collection in the form of interviews and direct observation. The informants taken by the researchers in this case were the service implementers of the East Lombok Disdukcapil and the people of East Lombok Regency as recipients of population administration services. The results of this study found that the innovation of online adminduk services with the "BAKSO" application at the Disdukcapil East Lombok was still not optimal. This is caused by inhibiting factors such as the minimal use of technology from the community, doubts about the validity of the input data, plus the age of the application which is still relatively new so that community participation in providing services is still not optimal. However, with this service innovation, the people of East Lombok Regency get convenience in population administration quickly, effectively, and efficiently. Keywords: Innovation, Service, Application of BAKSO